Understanding and preventing noncontact anterior cruciate ligament injuries: A review of the Hunt Valley II Meeting, January 2005 - Griffin, L. Y.; Albohm, M. J.; Arendt, E. A.; Bahr, R.; Beynnon, B. D.; DeMaio, M.; Dick, R. W.; Engebretsen, L.; Garrett, W. E.; Hannafin, J. A.; Hewett, T. E.; Huston, L. J.; et al. (The American Journal of Medical Sciences, 2006)
The incidence of noncontact anterior cruciate ligament injuries in young to middle-aged athletes remains high. Despite early diagnosis and appropriate operative and nonoperative treatments, posttraumatic degenerative arthritis may develop. In a meeting in Atlanta, Georgia (January 2005), sponsored by the American Orthopaedic Society for Sports Medicine, a group of physicians, physical therapists, athletic trainers, biomechanists, epidemiologists, and other scientists interested in this area of research met to review current knowledge on risk factors associated with noncontact anterior cruciate ligament injuries, anterior cruciate ligament injury biomechanics, and existing anterior cruciate ligament prevention programs. This article reports on the presentations, discussions, and recommendations of this group.